Socio-Lógica - Günther, Adolf (1955)
The word "socio-logic" has been intended to underline the existence of a logical nucleus in sociology, be it pure or applied, as well as in sociography. What distinguishes, from this point of view, the various sciences, is the type of logic used. Conceived as free from estimative judgments the sociology can chose the knowledge found in the social sciences, which is free from such judgment, but conceived as estimative science, she cannot adopt judgments encountered in the other fields of the social sciences, without thoroughly revising them. A sociologist must be at the same time "socio-logician" if he is to apply in the social field, the numerous independent and closed systems found impure sociology.